2020
DOI: 10.3390/polym12030525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fabric Weave on Thermal Radiation Resistance and Water Vapor Permeability

Abstract: In this work, aramid fibers were used to develop new, high-performance fabrics for high-temperature protective clothing. The research was based on the impact of the weave structure on fabric resistance to radiant heat. The goals of the research were primarily related to the development of new fabric structures created by the weave structure, which gives better protection of the body against high temperatures in relation to the standard weave structures that are used today. According to the results obtained it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
(21 reference statements)
2
5
0
Order By: Relevance
“…This affirms a study by Kiš et al. 38 on the influence of the weave and fabric structure on thermal radiation properties.…”
Section: Infrared Propertysupporting
confidence: 91%
See 1 more Smart Citation
“…This affirms a study by Kiš et al. 38 on the influence of the weave and fabric structure on thermal radiation properties.…”
Section: Infrared Propertysupporting
confidence: 91%
“…Further results indicate that fabric samples made of twill and diamond weave structures (A-2, B-2, A-3, B-3) relatively transmit body heat as compared to plain woven fabrics. This affirms a study by Ki s et al 38 on the influence of the weave and fabric structure on thermal radiation properties.…”
Section: Infrared Propertysupporting
confidence: 91%
“…Further, a study compared different weaves for aramid fabric with constant parameters (Content: 95% M-aramid Conex NEO + 5% P-aramid Twaron MOK3; Yarn fineness: 16.7 * 2 tex; Twist per meter: 323.2; Twist: S-twist) (Kis et al ., 2020). After the measurement of resistance to radiative heat (ISO 6492), fabric-volume porosity and water-vapor permeability, it was found that complex weaves including multi-weft and strucks weave had highest thickness and porosity resulting into highest thermal protection.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The increased thermal resistance indicates a strong barrier to metabolic body heat release generated in firefighting, thus resulting in more heat stress and thermal discomfort (Sun et al ., 2000). Kis et al . (2020) supported the inverse relation between thermophysiological comfort and fabric thickness by exhibiting the typical decrease in water vapor permeability with increase in fabric thickness.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Technical Textiles: Technical textiles represent the fastest increasing section in the clothing and textile industries, it can be seen as high added value applications [1]. Technical textiles are differentiated from other textiles in that they are made or designed to have specific functional properties and technical performance, rather than having decorative or aesthetic properties [2], [3]. Technical textiles can be referred to as functional textiles, industrial textiles, engineering textiles, performance textiles, and hi-tech textiles.…”
Section: Introductionmentioning
confidence: 99%